PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT BANK RAKYAT INDONESIA KANTOR CABANG PLUIT JAKARTA UTARA - Surahman Surahman; Purnomo Yanuarso, Bambang (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the Influence of Leadership Style and Work Discipline on Employee Performance at PT Bank Rakyat Indonesia Pluit Branch Office, North Jakarta, both partially and simultaneously. The method used in the study is the associative quantitative method. The sampling technique used is nonprobability sampling. The sampling method uses the saturated Sempling formula and the sample in this study amounted to 71 respondents. Data analysis uses validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, and hypothesis test. Based on the results of the multiple regression analysis calculation Y = 6.704 + 0.123X₁ + 0.724X₂. Based on the calculation of the classical assumption test, the regression model is free from multicollinearity, there is no heteroscedasticity, and is normally distributed. The correlation value is 0.820 which means that there is a strong relationship between Leadership Style and Work Discipline on Employee Performance. The coefficient of determination value is 0.672 or 67.2% while the remaining 32.8% is influenced by other factors. Based on the calculation of the t-test hypothesis, it is known that Leadership Style has an influence on Employee Performance, this is from the Hypothesis Test value obtained the t count value> t table or (4.311> 1.667). And for Work Discipline there is an influence on Employee Performance, this can be seen from the t count value> t table or (11.491> 1.667). Based on the calculation of the F-test hypothesis, it is known that the F count value> F table or (69.586> 3.13). Thus H0 is rejected and H1 is accepted, meaning that there is a significant simultaneous influence between Leadership Style (X1) and Work Discipline (X2) on Employee Performance (Y) at PT Bank Rakyat Indonesia Pluit Branch Office, North Jakarta